Underspending of capital expenditure at the Passenger Rail Agency of South Africa: current state of knowledge and a research agenda - Paine, Ayanda-Allie (Department of Social Development, 2025)
South Africa's passenger rail network is in a desperate state of disrepair, leaving commuters - many of whom form part of the poor or working class - even more destitute. The process of restoring or modernizing rail overhead cables, signalling, perway and other station infrastructure is extremely capital intensive. Passenger Rail Agency of South Africa (PRASA) has on numerous occasions been allocated a capital expenditure (CAPEX) budget by the National Treasury, specifically for the afore-listed capital projects. However, despite the availability of funding, the dire need for the capital projects as well as the urgency with which this implementation must take place, PRASA often grossly underspends the allocated CAPEX budget. Little research has been done on the entity's habitual underspending. The absence of the research into underspending of CAPEX at PRASA could affect the entity's ability to find sustainable solutions to the phenomenon. The purpose of this study was to summarize the state of our current knowledge of underspending of CAPEX at PRASA, identify further research needs and recommend areas that required additional probing by other scholars or organs of state. This was done through the collection of primary data from relevant experts and secondary data from applicable reports. For the primary data, semi-structured interviews were conducted with 13 industry experts. The secondary data comprised internal reports and other studies provided by the respondents. Thematic analysis was used to present the findings. The research respondents held varying views on the contribution of Treasury as well as internal systems towards underspending of CAPEX at PRASA, however, respondents were unanimous with regards to staff incapacity and corruption being factors which could be contributing to underspending at the entity. At a micro level, this study recommended that a skills audit be conducted by PRASA, to ascertain the capacity of its staff to spend on capital infrastructure. At a mezzo level, this study recommended that the Department of Transport review the efficacy of consequence management systems at PRASA. At a macro level, this study recommended that an external investigation be conducted into alleged corruption at PRASA.